Systemic risk in Danish banks: Implementing SRISK in a Danish context - Oliver Juhler Grinderslev; Kristian Loft Kristiansen (Danmarks Nationalbank, 2016)
The market-based SRISK measure introduced in Brownlees and Engle (2015) is used to measure the level of systemic risk in Danish banks and the Danish financial sector as a whole for the period 2005-15. The systemic risk contribution for a bank is measured as its propensity to be undercapitalized when a crisis occurs, i.e. when the system as a whole is undercapitalized. We find that SRISK was a very good predictor of which banks that needed public capital injections during the financial crisis of 2007-09 and that the market data generally provides useful information in times of crisis. According to SRISK, the Danish financial sector is well-capitalized as of end-2015. – – Det markedsbaserede SRISK mål, introduceret i Brownlees og Engle (2015), benyttes til at måle omfanget af systemisk risiko i danske banker og den danske finansielle sektor som helhed for perioden 2005-15. Det systemiske risiko-bidrag for en bank måles som bankens tilbøjelighed til at være underkapitaliseret i tilfælde af en krise, dvs. når systemet som hele er underkapitaliseret. Vi finder, at SRISK var en god fremadskuende indikator for hvilke banker som behøvede statslige kapitalindskud under finanskrisen i 2007-09 og at markedsdata generelt bidrog med brugbar information i krisetider. Ifølge SRISK er den danske finansielle sektor, vurderet ved slutningen af 2015, velkapitaliseret.
Keywords: C32; C53; G01; G21; G32; 330; SRISK; Structural GARCH; systemic risk; market-based indicator; Danish financial sector; financial crisis